HAKIKAT MANUSIA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Nisaa, Khoirun; Asrori, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to gain an understanding of the nature of human beings from the perspective of Islamic education. The purpose of this study was to describe the concept of human beings in the Qur'an, the process of their creation, and its implications for Islamic education. This study used a literature review method by examining relevant books, scientific articles, and Qur'anic interpretations. The results of the study show that humans in the Qur'an are described through various terms, such as al-Basyar, al-Insan, al-Nas, and bani Adam. In addition, the process of human creation is explained through systematic stages that demonstrate the perfection of Allah SWT's creation. This study concludes that Islamic education must integrate the aspects of divinity, humanity, and leadership in order to shape humans with character, piety, and responsibility as servants and caliphs on earth.